World Allergy Organization-McMaster University Guidelines for Allergic Disease Prevention (GLAD-P): Vitamin D. Issue 1 (December 2016) - Yepes-Nuñez, Juan; Fiocchi, Alessandro; Pawankar, Ruby; Cuello-Garcia, Carlos; Zhang, Yuan; Morgano, Gian; Ahn, Kangmo; Al-Hammadi, Suleiman; Agarwal, Arnav; Gandhi, Shreyas; Beyer, Kirsten; Burks, Wesley; et al.
Abstract Background The prevalence of allergic diseases is approximately 10 % in infants whose parents and siblings do not have allergic diseases and 20– 30 % in those with an allergic first-degree relative. Vitamin D is involved in the regulation of the immune system and it may play a role in the development, severity and course of asthma and other allergic diseases. Objective The World Allergy Organization (WAO) convened a guideline panel to develop evidence-based recommendations addressing the use of vitamin D in primary prevention of allergic diseases. Methods Our WAO guideline panel identified the most relevant clinical questions and performed a systematic review of randomized controlled trials and non-randomized studies (NRS), specifically cohort and case-control studies, of vitamin D supplementation for the prevention of allergic diseases. We also reviewed the evidence about values and preferences, and resource requirements (up to January 2015, with an update on January 30, 2016). We followed the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to develop recommendations. Results Having reviewed the currently available evidence, the WAO guideline panel found no support for the hypothesis that vitamin D supplementation reduces the risk of developing allergic diseases in children. The WAO guideline panel suggest not using vitamin D in pregnant women, breastfeeding mothers, or healthy term infants as a means of preventing the development of allergic diseases. This recommendation does not apply to those mothers and infants who have other indications for prophylactic or therapeutic use of vitamin D. The panel's recommendations are conditional and supported by very low certainty evidence. Conclusions WAO recommendations about vitamin D supplementation for the prevention of allergic diseases support parents, clinicians and other health care professionals in their decisions whether or not to use vitamin D in preventing allergic diseases in healthy, term infants.